Konsep Waris Anak Angkat dalam Wasiat Wajibah Perspektif KHI dan Prof. Wahbah Zuhaili - Nur Farikha; M. Ali Syaifudin Zuhri (Rechtenstudent, 2020)
When a human couple performs a marriage, then both are not blessed with a child. One way for the couple is to adopt a child, the law is fine as long as it fulfills the conditions prescribed by religion. This was done by the Prophet Muhammad. Adoption of children must meet state requirements, namely through court channels. Because something related to the rules certainly has a positive impact on the public, namely maslahah ummah. There are several legal consequences when someone is adopted as a child, one of which is if one of the adoptive parents or the adopted child has died there is an appreciation given by one of them. The author conducted this research to describe the concept of wills for adopted children in the distribution of inheritance according to KHI and Prof. Wahbah Zuhaili. The author in this study uses the analytical approach research method, namely an approach that is carried out by analyzing the thoughts of a character in this case Prof. Zuhaili, and its comparison with KHI. The conclusion found in this study is the wills of the compulsory will be something very new in Islam, especially when it comes to adopted children. Therefore, the concept of inheritance for adopted children is in the form of a mandatory will, which has been stipulated in the Islamic Law Compilation that a will when it is not disclosed by the adoptive parents, the adopted child will still receive a will, at most a third of the assets of the adoptive parents. Meanwhile, Prof. Wahbah Zuhaili stated that the will is obligatory for relatives and parents (people who are related by blood) because they are prevented from inheriting.